(untitled) (CIPEEX, 2025)
This case study examines the role of dance as a complementary therapeutic practice in improving the quality of life of individuals diagnosed with depression. Depression is a highly prevalent mental disorder worldwide, associated with persistent sadness, loss of motivation, social withdrawal, and reduced engagement in daily activities. While conventional treatments such as psychotherapy and pharmacological interventions remain the primary approaches, growing evidence highlights the benefits of integrative practices like dance. In this study, data were collected from a 21-year-old participant diagnosed with depression, through a semi-structured questionnaire addressing emotional, social, and physical dimensions of her experience with dance. The results demonstrated significant improvements in self-esteem, emotional regulation, social interaction, sleep quality, and motivation, as well as physical benefits including enhanced motor coordination and body awareness. Moreover, dance fostered a sense of belonging, resilience, and support, mitigating the effects of social isolation often associated with depression. These findings suggest that dance should be recognized not only as a form of physical activity but also as a valuable integrative strategy capable of promoting mental health, well-being, and overall quality of life among individuals experiencing depression.